Individual investors and local bias in the UK, 1870–19352. (30th March 2017) - Rutterford, Janette; Sotiropoulos, Dimitris P.; van Lieshout, Carry
Abstract: This article examines the long‐run evolution of local bias by UK investors between the 1870s and the 1930s. It uses a large sample of nearly 30, 000 shareholders based on 197 sets of share records, a large and representative database of the investor population across sectors and time. It investigates the structure and the evolution of local investment preference between shareholders and the companies in which they invested, as measured by the distance between where they lived and corporate headquarters. The study offers evidence of strong initial local investment preference, which declined over time for non‐Londoners, but remained strong for Londoners until the 1930s. Local investment preference of security holders was related to the size of the board of directors and, for wealthy investors, was related to the age of the firm. For large firms, local networks between investors and directors appear stronger when director shareholdings and voting rights were important. This study supports the analytical hypothesis of local informal trust networks between investors and directors as a means to overcome informational asymmetries and weak legal protection, and provides evidence that local preference was a means to curb insider opportunism and private benefits of control.